Analisis Perbedaan Antropometri Vertebra Thorax (T12) antar Kelompok Usia dengan Menggunakan Image CT Scan: Pendekatan Teknik Geometric Morphometric - Lutfi Gilangnugraha; Afiana Rohmani; Arief Tajally (Pusat Riset dan Inovasi Nasional, 2025)
The role of forensic anthropology is to identify the unknown skeletal remains to assiss in criminal investigation. Age estimation is one of the essential aspects of individual identification. Geometric morphometric is a technique to quantify the morphological of an object using the Cartesian coordinates of anatomical landmarks. There were no studies doing on the T12 vertebra for identification purposes using geometric morphometric techniques. This is an analytic observational study with a retrospective cross sectional study design. Samples were taken from 100 CT scan images at Radiology departemetnt of Dr Kariadi hospital. The age groups as independent variable, while both centroid size which represent the size and Principal component (PCs) which represent the size as the dependent variable. The differences between age group were analyzed using one way ANOVA test. There was a significant difference between age groups in the size of the T12 vertebra with p value = 0.003 (p<0.05). There was no significant difference in size between age groups in size, with p value = 0,149 (p>0,05). Using the Geometric morphometric approach, the vertebra T12 showed significant difference in size.